Research on the Impact of Used Automobile Oil Filters on the Soil and Natural Air - Holik, Yuri; Hanoshenko, Elena; Maksiuta, Nataliia (International Journal of Engineering and Technology, 2018)
The paper presents the results of studies of used automobile oil filters impact on the soil. The migratory properties of petroleum products, which are the used automobile oil part, are investigated in soil. The content of petroleum products and the damage from the placement of used automobile oil filters on the soil are defined. Â